2019
DOI: 10.1128/cmr.00060-18
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Pathobionts Associated with Inflammatory Bowel Disease

Abstract: SUMMARYGut bacteria play a key role in initiating and maintaining the inflammatory process in the gut tissues of inflammatory bowel disease (IBD) patients, by supplying antigens or other stimulatory factors that trigger immune cell activation. Changes in the composition of the intestinal microbiota in IBD patients compared to that in healthy controls and a reduced diversity of intestinal microbial species are linked to the pathogenesis of IBD. Adherent invasiveEscherichia coli(AIEC) has been linked to Crohn’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
191
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(202 citation statements)
references
References 167 publications
(198 reference statements)
6
191
3
2
Order By: Relevance
“…Although the exact cause of UC remains unclear, accumulating evidence has indicated that interaction between mucosal immunity and gut microbiota plays a key role in the pathogenesis of UC (Yue et al, 2019). Additionally, clinical studies have indicated that the composition of three major phyla of bacteria present in the gut microbiota of UC patients is disturbed, with a decrease in the proportion of Firmicutes and Bacteroidetes and an increase in that of Proteobacteria (Matsuoka and Kanai, 2015;Mirsepasi-Lauridsen et al, 2019). Administration of antibacterial agents and probiotics in UC patients has suggested that the gut microbiota does play a role in the onset of UC (Sokol, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact cause of UC remains unclear, accumulating evidence has indicated that interaction between mucosal immunity and gut microbiota plays a key role in the pathogenesis of UC (Yue et al, 2019). Additionally, clinical studies have indicated that the composition of three major phyla of bacteria present in the gut microbiota of UC patients is disturbed, with a decrease in the proportion of Firmicutes and Bacteroidetes and an increase in that of Proteobacteria (Matsuoka and Kanai, 2015;Mirsepasi-Lauridsen et al, 2019). Administration of antibacterial agents and probiotics in UC patients has suggested that the gut microbiota does play a role in the onset of UC (Sokol, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, fecal levels of several commensal bacteria, including Veillonella spp., E. coli, and Fusobacterium spp., were positively associated with inflammation biomarkers in the current study. All of those bacteria were considered as invasive [38][39][40], and high levels were reported previously in IBD patients [23,28,31,33,[41][42][43][44][45]. Changes in Prevotella spp.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the presence of E. coli varied based on the location on the lab coat. In the literature, it has been associated with numerous diseases, such as in ammatory bowel disease 26 , Crohn's disease 27 , UTIs 28 , and pediatric acute diarrhea. 29 In the current study, the distribution of bacterial growth was highest on the mid-sleeve area healthcare personnel attire, in which mid-sleeves are close to the sides of uniforms.…”
Section: Discussionmentioning
confidence: 99%